An intra-neural microstimulation system for ultra-high field magnetic resonance imaging and magnetoencephalography - Glover, Paul M.; Watkins, Roger H.; O’Neill, George C.; Ackerley, Rochelle M.; Sánchez-Panchuelo, Rosa-Maria; McGlone, Francis; Brookes, Matthew J.; Wessberg, Johan; Francis, Susan T. (Elsevier, 2017)
Background